Functional Aspect of Seating furniture at Taman Fatahillah, Jakarta - Octaviana Sylvia Caroline; Bambang Kartono; Yunida Sofiana; Titi Indahyani (Bina Nusantara University, 2019)
The goal of this research was to add visual-captured data and analytical from the aspects of function as inputs for designers to be able to propose design on revitalizing the area of Taman Fatahillah. There were two problems that had been found. First, the historical street furniture had not been thought to be part of a new development of the area. Second, the newly added street furniture had not been integrated into the original purpose of Taman Fatahillah. The research used qualitative descriptive methodology with observation and visual-captured methods to collect all data needed. The conclusions are the seating furniture from the old plan has been changed its function, some of them function properly, and one of them does not function properly. Part of the newly added seating furniture in this area functionally works, but one of them does not functionally integrate into the surroundings of Taman Fatahillah as a historical revitalized public area.